Determinação do coeficiente de decaimento bacteriano em wetland - alagado construído - Beda, Juliana Neves (2011)
Wetlands systems are considered nowadays as a treatment method that uses simple, easy operation and low cost technology, which has been used in various parts of the world and also in Brazil. Used alone or as a complement to other types of treatment systems, once it effectively removes nutrients, pathogens and other pollutants in the water. Due to the high complexity found in wetlands, making it difficult to predict the response of the system to treat wastewater, one should consider as ideal to base the sizing of the wetland system over the necessary removal of this parameter instead of scaling it from empiricism. The study was conducted to determine the coefficient of bacterial decrease in the Wetland unit located at Ponta Negra Station Sewage Treatment, located in Natal, the coastal region of Rio Grande do Norte. The most representative model to determine the bacterial decrease in this system was the one from Chick for hydraulic piston system. Kb of 0.37 d-1 were found for the flow rate of 15m³/d, while for the system operating at maximum design flow, 30m³/d, the Kb of 0.98 d-1 was found